Immediate Breast Reconstruction Using the Goldilocks Procedure: A Balance between More Surgery and Patient Satisfaction. Issue 4 (31st January 2022) - Manrique, Oscar J.; Kuruoglu, Doga; Yan, Maria; Bustos, Samyd S.; Boughey, Judy C.; Harless, Christin A.; Tran, Nho V.; Martinez-Jorge, Jorys; Forte, Antonio J.; Nguyen, Minh-Doan T.
Abstract : Background: Since its first description in 2012, the Goldilocks procedure has become an option for immediate breast reconstruction, particularly for obese patients who are poor candidates for traditional implant or autologous reconstruction. In this work, the authors performed a longitudinal study of patients who underwent mastectomy with Goldilocks reconstruction to assess the incidence of additional surgical procedures, and to assess surgical outcomes and patient satisfaction. Methods: A retrospective review of patients who underwent mastectomy with the Goldilocks procedure only at Mayo Clinic Rochester between January of 2012 and September of 2019 was performed. Demographics, complications, additional breast procedures performed to attain the final results, and patient-reported outcomes using the BREAST-Q were recorded. Univariate and multivariable analyses were performed to identify statistical associations and risk factors. Results: Sixty-three patients (108 breasts) were included. Mean age was 57.8 years. Mean body mass index was 37.6 kg/m 2 . Median follow-up time after the mastectomy with the Goldilocks procedure was 15 months. The major complication rate within the first 30 days was 9.3 percent. Forty-four breasts (40.7 percent) underwent additional surgery. Dyslipidemia was significantly associated with an increased risk of additional surgery (adjusted hazard ratio, 2.00; p = 0.045). Scores in the four BREAST-Q domains were not statistically different between patients who had additional procedures and those who did not. Conclusions: Based on the results, the authors recommend a thorough preoperative discussion with patients who are candidates for the Goldilocks procedure to explore all options for reconstruction and their expectations, because it is crucial to reduce the necessity for additional operations in this high-risk population. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.